Automatização de um processo de negócio de uma operadora de planos de saúde, utilizando BPMS - Coelho, Juliana de Medeiros (2018)
This present study approaches a business process transformation through automation in a health insurance company located in Fortaleza - Ceará. The automation process was implemented to improve the workflow performance, check record’s tracking and ensure to attend promply requests. The claim registration process has been done without standards presenting many manual activities including physical evidencies (paper registration). Thus, this process affects the customers expectation about the service and good results. The BPMS, which consists in a system of business process management, was chosen as a solution because allows operational acting through automation, implying on safety, agility, control and compliance to the process. The main objective of this study is to evaluate the system’s implementation, analyzing its usability and pratical adherence. The customer’s satisfaction results will be discussed after the transformed workflow process standardization. The project can be inferred as successful because the way as the new process has behaved overcame all the expectations from operational and management perspectives.